2019
DOI: 10.1111/ctr.13508
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best predictor of de novo donor‐specific antibodies in a cohort of non‐sensitized first kidney transplantation: Antigenic, allelic, epitope, or physiochemical HLA mismatches?

Abstract: Background Assessment of human leukocyte antigen (HLA) matching by using high‐resolution allele typing and knowledge of HLA molecule structure may lead to better prediction of de novo donor‐specific antibody (dnDSA) development. Methods We conducted a single‐center cohort study among 150 non‐sensitized first kidney transplant recipients to compare the association between antigenic (Ag), allelic (Al), eplet (Ep), amino acid (AAMS) HLA matching and electrostatic (EMS) and hydrophobic (HMS) mismatch scores, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We found that analyses of both B cell and T cell epitopes (i.e., eplet mismatches and PIRCHE scores, respectively), had positive predictive capabilities with respect to de novo DSA production. Recent studies reported strong associations of eplet mismatch and/or PIRCHE-II scores with de novo DSA production or graft outcomes (25,26,34,35), whereas it was also reported that allelic and epitope mismatch analysis presented no additional value with respect to risk management (36). Differences in immunogenicity might be dependent on the nature of the eplet and the precise mismatch position (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…We found that analyses of both B cell and T cell epitopes (i.e., eplet mismatches and PIRCHE scores, respectively), had positive predictive capabilities with respect to de novo DSA production. Recent studies reported strong associations of eplet mismatch and/or PIRCHE-II scores with de novo DSA production or graft outcomes (25,26,34,35), whereas it was also reported that allelic and epitope mismatch analysis presented no additional value with respect to risk management (36). Differences in immunogenicity might be dependent on the nature of the eplet and the precise mismatch position (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…To determine which DSAs are clinically important, their precise specificities defined as donor epitope specific antibodies (DESAs) may be important to examine. An eplet or functional HLA epitope—a concept introduced by Duquesnoy 19 —is defined as a cluster of polymorphic amino acid configurations within a 3.0–3.5 Å radius that is needed to induce an antibody response, and that these epitopes may be identical on different HLA molecules 20,21 . Literature showed that the number of HLA epitope mismatches has been associated with poor graft function in different types of solid organ transplantation 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…An eplet or functional HLA epitope-a concept introduced by Duquesnoy 19 -is defined as a cluster of polymorphic amino acid configurations within a 3.0-3.5 Å radius that is needed to induce an antibody response, and that these epitopes may be identical on different HLA molecules. 20,21 Literature showed that the number of HLA epitope mismatches has been associated with poor graft function in different types of solid organ transplantation. 22,23 However, the clinical relevance of DESAs recognizing epitopes shared between different HLA molecules, compared with DSA, has not been defined yet.…”
Section: Introductionmentioning
confidence: 99%
“…Eplets are a cluster of polymorphic amino acid configurations within a 3.0-3.5 Å radius that is hypothesized to be sufficient to induce an antibody response, when mismatched in a transplant setting. 3,4 Various tools are available to determine eplets mismatches, including the ElliPro epitope predictor program. This online algorithm combines a modified version of Thornton's method, that identifies structural epitopes based on protrusion from the antigen surface, 5 with a residue clustering algorithm.…”
Section: Introductionmentioning
confidence: 99%